Occupied Space. (November 2013) - Rice, Louis; Mosley, Jonathan; Sara, Rachel
Abstract With the rapid privatisation of urban space worldwide, architecture has become an increasingly political issue. The Occupy Movement, which set up encampments in over half the cities in the world during 2011 to protest against social and economic inequality, understood the power of physical occupation. Architect and lecturer Louis Rice describes how the potency of such expression lies not in its form – temporary tents and makeshift structures – but in its potential to challenge the current power base and reconceptualise the city.